Medwave’S Editorial History, Policies and Guidelines: 3. Section Policies [Historia, Política y Normas de Medwave: 3. Normas de Sección] - Bachelet-Norelli, V (2017)
This article is the third of a series of four editorials that report on Medwave’s policies, including section policies, formal requisites according to article type, and guidelines for reviewers and authors, with special emphasis on publication and research ethics. The journal believes that it is important to publish its policies in the format of editorials in order to facilitate and ensure dissemination to our broader readership. This editorial describes the types of articles that the journal publishes, such as primary studies, review articles, case reports, letters, and commentaries, among others.Este artículo corresponde a la tercera parte de una serie de cuatro editoriales que reportan acerca de las políticas de Medwave, incluyendo las políticas de secciones, los aspectos formales según tipo de trabajo y las orientaciones generales para autores y revisores, poniendo especial énfasis en la ética de las publicaciones y de la investigación. La revista considera que es importante publicar sus políticas como editoriales para asegurar su debida difusión entre nuestros lectores. El presente editorial describe los tipos de artículos que publica la revista, como estudios primarios, artículos de revisión, reportes de casos, cartas, comentarios, entre otros.